2006
DOI: 10.1136/oem.2006.029017
|View full text |Cite
|
Sign up to set email alerts
|

Heat-related and cold-related deaths in England and Wales: who is at risk?

Abstract: Background: Despite the high burden from exposure to both hot and cold weather each year in England and Wales, there has been relatively little investigation on who is most at risk, resulting in uncertainties in informing government interventions. Objective: To determine the subgroups of the population that are most vulnerable to heat-related and coldrelated mortality. Results: A risk of mortality was observed for both heat and cold exposure in all regions, with the strongest heat effects in London and stronge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

41
380
7
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 534 publications
(445 citation statements)
references
References 52 publications
41
380
7
8
Order By: Relevance
“…Previous studies reported that temperature-related mortalities are more pronounced in the elderly (Revich and Shaposhnikov 2008;Anderson and Bell 2009). However, the heterogeneity among different age groups is worth further examination (Hajat et al 2007;Baccini et al 2008;Ishigami et al 2008). In this study, we investigated both effects of heat and cold temperatures on different types of mortality (including non-accidental, cardiopulmonary, cardiovascular, and respiratory) and age-specific non-accidental mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported that temperature-related mortalities are more pronounced in the elderly (Revich and Shaposhnikov 2008;Anderson and Bell 2009). However, the heterogeneity among different age groups is worth further examination (Hajat et al 2007;Baccini et al 2008;Ishigami et al 2008). In this study, we investigated both effects of heat and cold temperatures on different types of mortality (including non-accidental, cardiopulmonary, cardiovascular, and respiratory) and age-specific non-accidental mortality.…”
Section: Introductionmentioning
confidence: 99%
“…There are spatial patterns to the distribution of vulnerability to high temperatures; for example, urban residents are more exposed (Hajat et al 2007) and within towns and cities it is often deprived areas that are most likely to be located within the center of urban heat islands (UHIs). Deprived inner-city communities are also less likely to have close access to cool spaces such as green parks, gardens, or woodlands.…”
Section: Vulnerability To High Temperaturesmentioning
confidence: 99%
“…For instance, a study conducted in England and Wales found an association between cold temperature and mortality [10]. Also, in central Europe, it was observed an increased mortality with temperature at low average daily temperatures [11].…”
Section: Resultsmentioning
confidence: 99%